2018
DOI: 10.1002/ijc.31547
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic and targetable genetic alterations in 70 urachal adenocarcinomas

Abstract: Urachal cancer (UrC) is a rare but aggressive malignancy often diagnosed in advanced stages requiring systemic treatment. Although cytotoxic chemotherapy is of limited effectiveness, prospective clinical studies can hardly be conducted. Targeted therapeutic treatment approaches and potentially immunotherapy based on a biological rationale may provide an alternative strategy. We therefore subjected 70 urachal adenocarcinomas to targeted next-generation sequencing, conducted in situ and immunohistochemical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 37 publications
7
50
0
5
Order By: Relevance
“…For UAC, several studies have been published which mainly focus on current therapeutic targets [11][12][13][14][15][16]. Reis et al identified, for instance, various druggable alterations (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For UAC, several studies have been published which mainly focus on current therapeutic targets [11][12][13][14][15][16]. Reis et al identified, for instance, various druggable alterations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the pathogenesis of BAC remains poorly understood, and morphological resemblance to colorectal adenocarcinomas (CORAD) suggests potential analogies. Nextgeneration sequencing (NGS) data have improved our knowledge of genetic driver alterations in urothelial carcinomas [7] and CORAD [8], and first NGS data are now available for rare BAC [9,10] and UAC [11][12][13][14][15][16]. Additionally, a few single gene sequencing reports for BAC and UAC (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic options include (partial) cystectomy with en bloc resection of the median umbilical ligament and umbilicus in local disease and mostly 5-fluorouracil-based chemotherapy regimes in advanced cases [5][6][7]. Recently, molecular studies have allowed more insights in the genetic background of UrC, which seems to be a distinct molecular entity [8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Next-generation sequencing was performed on 70 urachal carcinomas and showed mutations in TP53, KRAS, BRAF and PIK3CA, which are commonly mutated in colon cancer [107]. In a series of 12 urachal adenocarcinomas analyzed by targeted exon sequencing and transcriptome profiling, investigators found that urachal adenocarcinoma closely resembles colorectal cancer with a subset of cases showing a microsatellite unstable phenotype.…”
Section: Urachal Carcinomamentioning
confidence: 99%
“…In a series of 12 urachal adenocarcinomas analyzed by targeted exon sequencing and transcriptome profiling, investigators found that urachal adenocarcinoma closely resembles colorectal cancer with a subset of cases showing a microsatellite unstable phenotype. A single patient in this series underwent treatment with immune checkpoint blockade, resulting in stabilization of their metastatic disease [107][108][109].…”
Section: Urachal Carcinomamentioning
confidence: 99%